2002
DOI: 10.1067/mva.2002.126542
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of failure in the treatment of type II endoleak with percutaneous coil embolization

Abstract: PTCE of type II endoleaks has a high failure rate because of multiple anatomic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 30 publications
2
73
0
2
Order By: Relevance
“…Transarterial retrograde embolization as well as translumbar embolization was performed for patients with sac enlargement of more than 5 mm, but the technical success rate was not high (17%-44%) because of the presence of a multitude of collateral networks of aortic side branches. [18][19][20] Identification of patients at increased risk of persistent type II endoleak is still imprecise, and the occurrence of various associated adverse events has prompted some interventionists to come to accept that the best method for handling a type II endoleak is to prevent its development in the first place. Muthu, et al reported the findings of their study of routine preoperative embolization of the IMA and thrombin injection into the aneurysm sac.…”
Section: (A) (D) (E) (B) (C)mentioning
confidence: 99%
“…Transarterial retrograde embolization as well as translumbar embolization was performed for patients with sac enlargement of more than 5 mm, but the technical success rate was not high (17%-44%) because of the presence of a multitude of collateral networks of aortic side branches. [18][19][20] Identification of patients at increased risk of persistent type II endoleak is still imprecise, and the occurrence of various associated adverse events has prompted some interventionists to come to accept that the best method for handling a type II endoleak is to prevent its development in the first place. Muthu, et al reported the findings of their study of routine preoperative embolization of the IMA and thrombin injection into the aneurysm sac.…”
Section: (A) (D) (E) (B) (C)mentioning
confidence: 99%
“…11,13,14,18-20 Others, however, report a benign clinical course of type II endoleaks. 16, 21 In our study, type II endoleaks were significantly associated with sac growth and reduction.…”
Section: Discussionmentioning
confidence: 69%
“…Treatment options include percutaneous transluminal coil embolisation [11], intra-arterial embolisation [12], and-more specifically in the case of IAAs-percutaneous transosseous embolisation [13]. The technique of laparoscopic branch ligation has been suggested as an alternative for the treatment of Type II endoleaks by some experienced investigators [14], particularly in cases of failed embolisation.…”
Section: Discussionmentioning
confidence: 99%